Investigation of bending and compression properties on PLA-brass composite using FDM - S. K., Selvamani; W. K., Ngui; K., Rajan; M., Samykano; R., Reji Kumar; Badadhe, Avinash M. (Elsevier Ltd., 2022)
Fused Deposition Modeling (FDM) is often favored over conventional techniques as it can produce highly accurate three-dimensional models with minimal material waste. Nevertheless, in FDM, the mechanical properties of different materials used in the FDM process are of ongoing interest. Since the properties of brass alloys in the FDM process are still lacking, the present study focuses on the bending and compression properties of the FDM printed part with 15Â wt and 70Â wt of brass-reinforced polylactic acid (PLA) and various infill patterns. The specimen preparation and testing were carried out accordingly to ASTM D790 and ASTM D695, respectively. The impact of five different infill patterns and two different compositions on the bending and compression properties was also analyzed using response surface methodology. A prediction model is then developed to predict the desired bending and compression properties. Results show that the 15Â wt of brass composition specimens have better properties compared with the 70Â wt of brass composition. This is due to an increase in the wt of brass composition, which resulted in lower interlayer adhesion energy with the PLA. It was also found that the concentric and grid pattern are the best printing pattern for bending and compression properties, respectively.